2005
DOI: 10.1093/ps/84.10.1533
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary folic acid supplementation on egg folate content and the performance and folate status of two strains of laying hens

Abstract: Enrichment of eggs with folate is possible when dietary folic acid levels are increased. However, development of optimal strategies for the production of folate-enriched eggs requires knowledge as to differences due to strain of bird and a greater understanding of the factors limiting egg folate deposition. To this end, a study was designed to determine the response of two leghorn strains that differ in production performance. Hyline W36 and W98 hens (n = 6 per diet) received a barley-based ration containing 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
55
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 19 publications
10
55
5
Order By: Relevance
“…In the present study, yolk folate content in the hens fed 10.31 mg folate/kg diet was higher by about 40% than that in the hens fed a basal diet (0.31 mg/kg diet). This result agrees with the report of Hebert et al (2005) that maximal egg folate levels were achieved when dietary folate concentrations exceeded the recommendation of 0.25 mg of folate/kg of diet given by NRC (1994). Sherwood et al (1993) reported that the normal folate concentration in egg yolk is approximately 43-fold higher than that in blood plasma from which yolk folate is taken up.…”
Section: Vitamin Levels Measured In Liver Serum and Egg Yolksupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, yolk folate content in the hens fed 10.31 mg folate/kg diet was higher by about 40% than that in the hens fed a basal diet (0.31 mg/kg diet). This result agrees with the report of Hebert et al (2005) that maximal egg folate levels were achieved when dietary folate concentrations exceeded the recommendation of 0.25 mg of folate/kg of diet given by NRC (1994). Sherwood et al (1993) reported that the normal folate concentration in egg yolk is approximately 43-fold higher than that in blood plasma from which yolk folate is taken up.…”
Section: Vitamin Levels Measured In Liver Serum and Egg Yolksupporting
confidence: 92%
“…This result indicates that laying hens have highly efficient conservation and delivery systems for folate (Sherwood et al 1993). The result that egg yolk and serum folate concentrations reached saturation when hens were supplemented with a very high level of dietary folate agrees with the findings by Hebert et al (2005) and Sherwood et al (1993) that the saturation of plasma folate concentrations represents a putative control point for egg folate concentrations. However, House et al (2002) reported that the saturation limit of egg folate content was not due to limitations in transport processes from serum to egg yolk.…”
Section: Vitamin Levels Measured In Liver Serum and Egg Yolksupporting
confidence: 83%
See 1 more Smart Citation
“…Hens fed a commercial, folate-sufficient diet (0.72 mg folate/kg) produced eggs with slightly less than half of the maximal folate content. However, when laying hens were supplemented with 0, 2, 4, 8, 16, 32, 64 or 128 mg/kg of crystalline folic acid for 21 days, laying performance was not affected (Hebert et al, 2005). Considering plasma homocysteine concentrations, a strain-specific requirement for folic acid could be deduced as the higher egg mass producing strain benefited from increased folic acid through a reduction in plasma homocysteine concentrations.…”
Section: Folic Acid (Pteroylglutamic Acid)mentioning
confidence: 97%
“…These strategies include the development of novel foods enriched with natural folates (12) . Recently, several groups have shown that the folate content of eggs can be increased significantly by supplementing the diet of laying hens with folic acid (43)(44)(45)(46)(47)(48) . Most of the additional folate appears in the eggs in the natural form, mainly as 5-methyltetrahydrofolate (48) .…”
mentioning
confidence: 99%